Comparative Study on Emotional Intelligence in Alpine Skiing Versus Football - T.C. Stan (Simon); V. Koronas; D.I. Tohanean (Editura Universitatii Transilvania din Brasov, 2022)
This paper aims to highlight possible differences in the component of emotional intelligence in two distinct categories of athletes: alpine skiers, versus football players, at the youth level. A battery of specific tests was applied only once, the results found indicated more significant values for skiers. The significance of these results leads us to the idea that the characteristics of the sport and its practice at the level of performance significantly influence the level of emotional intelligence. The general conclusion drowns significant differences in the component of emotional intelligence between skiers and athletes footballers.